Growing biofuel demand in Thailand and Malaysia: water use and impacts. Project report submitted to Food and Agriculture Organization (FAO) under the project, "Comparative assessment of water usage and impacts arising from biofuel projects in SOUTHEAST ASIAn Countries? - Amarasinghe, Upali A.; Eriyagama, Nishadi; Soda, Wannipa (International Water Management Institute, 2010)
Report submitted to Food and Agriculture Organization (FAO) under the project, "Comparative assessment of water usage and impacts arising from biofuel projects in SOUTHEAST ASIAn Countries?, commissioned by the Letter of Agreement No LOA/RAP/2009/38. Thailand and Malaysia are two SOUTHEAST ASIAn countries with rapidly growing biofuel demand. Increasing use of biofuel envisages reducing dependence of petroleum products for transport and mitigating environmental impacts by reducing carbon emissions. It also expects to contribute to rural development and poverty reduction. However, the impacts of expanding production of feedstock for biofuel on water supply are not well understood. This paper assesses the water footprints and impacts of sugarcane molasses and cassava based bioethanol in Thailand, and palm oil based biodiesel in Malaysia. The water footprint of a commodity or service is the water depleted in its life cycle of its production or consumption. The total water footprints of sugarcane molasses and cassava bioethanol production in Thailand are estimated to be 1,646 and 2,304 m3/tonne, respectively, and of palm oil biodiesel in Malaysia is 3,730 m3/tonne. However, the contributions from irrigation are only a small fraction --9.0, 0.7 and 0.3%-- of the total water footprints of molasses and cassava bioethanol, and palm oil biodiesel respectively. In terms of irrigation water use,cassava is a better feedstock for bioethanol production than sugarcane molasses. In Thailand, the total annual irrigation water footprints in bioethanol production --54 million m3 (mcm) for molasses and 15 mcm for cassava-- is only 0.02% of the total renewable water resources. In Malaysia, total annual irrigation water footprint of palm oil biodiesel production is only 0.001% of the total renewable water resources. A significant spatial variation of irrigation water footprints of molasses based ethanol exists across provinces in Thailand, indicating potential for reducing water footprints. The total irrigation water footprints in biofuel production in the future in both countries will also be negligible in comparison to total water availability. However, the impact of wastewater generated in the production processes can have significant impacts on quality of local water resources. A part of the waste water, called 'spent wash', is applied as fertilizer, and over use of it can affect soil and neighboring water resources. The proposed plans on biofuel production in the future can generate more 'spent wash' than that can be used in crop fields as fertilizer. Spent wash has found to have high PH value, temperature, biological and chemical oxygen contents etc. The usual practice of storing spent wash in a pond for a long period near a plant can have detrimental impact on soil, streams' and groundwater quality. In sum, this study concludes that from the perspective of quantity of irrigation water use, the increasing biofuel production does not pose a major problem in Thailand or in Malaysia, and cassava is a better feedstock than sugarcane molasses for bioethanol production. However, the quality of water resources with increasing effluents generated by the biofuel plants could be a major environmental bottleneck to guard against.